2016
DOI: 10.1007/s10620-016-4426-5
|View full text |Cite
|
Sign up to set email alerts
|

AGY, a Novel Egg Yolk-Derived Anti-gliadin Antibody, Is Safe for Patients with Celiac Disease

Abstract: In our cohort, AGY was safe and potentially associated with improved CD-related outcome measures in patients on a GFD. A larger study powered for further safety and efficacy evaluation is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 22 publications
0
17
0
2
Order By: Relevance
“…In a very preliminary pilot study published in this issue of Digestive Diseases and Sciences, Sample and colleagues report their experience with AGY, a specific chicken egg yolk-derived immunoglobulin (IgY) against wheat gliadin on a cohort of ten patients with biopsy-proven CD with the aim of assessing its safety in adult CD individuals already consuming a GFD for at least 6 months [9]. Previous preclinical studies performed by the same authors demonstrated that this polyclonal antibody is able to neutralize gliadin in the presence of simulated gastrointestinal fluids in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In a very preliminary pilot study published in this issue of Digestive Diseases and Sciences, Sample and colleagues report their experience with AGY, a specific chicken egg yolk-derived immunoglobulin (IgY) against wheat gliadin on a cohort of ten patients with biopsy-proven CD with the aim of assessing its safety in adult CD individuals already consuming a GFD for at least 6 months [9]. Previous preclinical studies performed by the same authors demonstrated that this polyclonal antibody is able to neutralize gliadin in the presence of simulated gastrointestinal fluids in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Taking AGY capsules has been shown capable to reduce gliadin absorption from 42.8% to 0.7% in an animal study [47]. A clinical trial with AGY also obtained effectiveness [48].…”
Section: Prevention Of Gluten Degradationmentioning
confidence: 97%
“…Ten patients completed the study, and no safety concerns were identified. Most patients had fewer celiac symptoms, improved quality of life, lowered antibodies, and lowered lactulose mannitol ratio when taking AGY as compared to the baseline run-in period (85).…”
Section: Novel Therapies For Celiac Diseasementioning
confidence: 99%